Pengujian efek kualitas dan risiko keamanan pada intensi pembelian makanan dengan mediasi traceability - Hetty Karunia Tunjungsari; Kennedy Lianto; Chairy Chairy (Universitas Kristen Maranatha, 2021)
There are several consumer considerations in buying and consuming food such as the quality and safety of the food and traceability of the food itself. This study examines the effect of food quality and perception of food risk on purchase intention. We also examine mediating effect of traceability in the influence of quality and safety on consumer purchase intentions. The survey was conducted online to obtain data consisting of 100 fast food consumers. The research hypothesis testing was carried out using SmartPLS statistical software. The results showed food quality and perception of food risk have significant influence on purchase intention. However, there was no mediating effect of traceability in the influence of food quality and safety on consumer purchase intentions. This research theoretically expands the literature in the field of consumer behavior, particularly related to food marketing. The results of this study can practically be used as a basis for formulating food marketing strategies, especially related to steps that can be used to maintain food quality, safety, and traceability as an effort to increase consumer purchase intentions.